THE EPISTEMOLOGICAL PERSPECTIVE OF FRACTIONAL RESERVE BANKING AND FULL RESERVE BANKING: WHERE ISLAMIC BANKING SHOULD STAND? - Yaser Taufik Syamlan (Institute for Research and Community Empowerment (LPPM TAZKIA), 2016)
Objectives – this research is aimed to compare those epistemological bases to the mindset of Islamic Bank and try to drive the philosophy in practical operation whether based on the Fractional Reserve Banking Sytem (RBS) or 100% RBS and analyze the challenges in deploying the 100%RBS. Methods - This research will be conducted based on an extensive literature review.Results - Based on the epistemological analysis of money and the business cycle as well as the views of Islamic scholars, 100%RBS should be the best for Islamic Bank. There are four types of 100% RBS namely Pure Commodity Money, Sovereign Money, Narrow Banking, and Limited Purpose Banking. To deploy it into the economic system, another philosophical work should be done to choose one of the types and strengthen it so that the theory of 100%RBS can be implemented for the goodness of Islamic Bank. Conclusion - In Conclusions, Based on the epistemology defined by Islamic Scholars, FractRBS has more mafsadah if we compare to the maslahah. Therefore, 100% RBS should be better for the Islamic Bank.